Biodiversity-based Land Management Strategies for Food Security in Suburban Areas - Soelistianto, Farida Arinie (Westscience Press, 2025)
This study examines biodiversity-based land management strategies as a sustainable solution to urban food security challenges in Indonesia. Using a qualitative approach and the Penta Helix model, data from five informants representing academia, government, private sector, community, and media were analyzed. Findings highlight the significant contributions of each stakeholder in promoting biodiversity, from academic research and innovative policies to community-driven urban farming initiatives and media advocacy. Synergies among stakeholders were evident, but challenges such as resource constraints, policy fragmentation, and cultural resistance persist. Case studies from local and global contexts underline the transformative potential of integrating biodiversity into urban planning. The study concludes that biodiversity-based strategies, supported by collaborative governance, are essential for achieving sustainable and food-secure urban environments in Indonesia.